Identifying self-care behaviour and its predictors among type 2 diabetes mellitus patients at a district of Northern Peninsular Malaysia - Kang, Chia Yee; Md Said, Salmiah; Abdul Manaf, Rosliza (Faculty of Medicine and Health Sciences, Universiti Putra Malaysia, 2018)
Introduction: The prevalence of diabetes mellitus among Malaysian aged ≥ 18 years increased from 11.6% (2006) to 17.5% (2015). Positive self–care behaviour leads to good glycaemic control. The objective of this study is to determine the self-care behaviour, its associated factors and predictors among type 2 diabetes mellitus (T2DM) patients in government health clinics at a district of Northern Peninsular Malaysia. Methodology: A cross-sectional study was conducted on 546 T2DM patients aged ≥ 18 years, recruited by simple random sampling method. A validated self-administered questionnaire including socio-demographic characteristics, diabetes profile, knowledge, Health Belief Model (HBM) and Summary of Diabetes Self-care Activity Scale (SDSCA) was used. Data were analysed using SPSS version 22.0. Self-care behaviour is the dependent variable. Results: The respondents practised 3.4 (SD = 1.11) days self-care behaviour past 1 week. The predictors of self-care behaviour were self-efficacy (standardized β= 0.257, p< 0.001), knowledge (standardized β= 0.112, p= .007), female (standardized β= 0.107, p= 0.010), combination oral hypoglycaemic agents (OHA) and insulin (standardized β= -0.182, p= 0.002), and monthly income < RM1,000 (standardized β= -0.129, p= 0.002). The entire group of variables significantly predicted self-care behaviour [F (6, 539) = 15.79, p< 0.001, adjusted R2 = 0.140] with total variance of 14.9%. Self-efficacy was the strongest predictor in self-care behaviour. Conclusion: The findings enable us to identify the specific groups with predicted lower self-care behaviour which are useful in future planning and implementation of intervention.